STRUCTURE OF RFID-BASED WAREHOUSE MANAGEMENT SYSTEM (Modern education and development, 2025)
This thesis is dedicated to studying the structure of an RFID (Radio Frequency Identification) based warehouse management system. The research analyzes the system’s core components—RFID tags, readers, and software. It also examines the system’s integration into warehouse processes, real-time inventory tracking capabilities, and technical requirements. The efficiency, advantages, and limitations of RFID systems are evaluated. The study highlights the importance of RFID in advancing warehouse automation and reducing operational costs. Future integration with IoT and artificial intelligence could further enhance the system’s capabilities.